Seeking Authenticity in Place, Culture, and the Self - Osbaldiston, N. author. aut Link
XI, 175 p. 4 illus.
Keywords: In recent times, there has been a substantial push by people to escape the metropolis for lifestyles in small coastal, country, or mountainside locales. This book explores the narratives emerging from amenity-left migration using methods developed within the 'strong' cultural sociology.